PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN KOMUNIKASI TERHADAP KINERJA PENGELOLA LKM MBT PADA KAWASAN KOTA TERPADU MANDIRI DI KTM BELITANG KABUPATEN OGAN KOMERING ULU TIMUR PROPINSI SUMATERA SELATAN - Elvie Maria; Yos Karimudin (JURNAL ILMIAH KOHESI, 2018)
The purpose of this research was to determine the effect of organizational culture,, leadership andcommunication to the managers performance. The population of this study was 114 managerial (MFIBMT) in the Integrated Urban Self Area in Belitang, The Regency of Ogan Komering Ulu Timur, SouthSumatra Province.The method used in this research was correlational that determines the level of influence ofdifferent variables with sample 98 using proportionate random sampling technique. Data processingused namely by SPSS 24. Research instruments consisting of engineering data analysis and thehypothesis. The results of the study states that contribution variable leadership, organizational culture,and communication , to explain manager performance variables is 74.9%, and explained that leadership,organizational culture, and communication awarded to managers simultaneous had links and realimpact of the manager performance